2007
DOI: 10.1542/peds.2006-2528
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Bedside Rounds: A New Approach to Patient Care and Teaching

Abstract: The importance of patient-centered care and the role of families in decision-making are becoming more recognized. Starting with a single acute care unit, a multidisciplinary improvement team at Cincinnati Children's Hospital developed and implemented a new process that allows families to decide if they want to be part of attending-physician rounds. Family involvement seems to improve communication, shares decision-making, and offers new learning for residents and students. Despite initial concerns of staff mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(218 citation statements)
references
References 13 publications
(14 reference statements)
6
209
1
2
Order By: Relevance
“…In this way, having a clear understanding of membership can increase the likelihood that people with relevant knowledge will be included in discussions, a necessary first step to ensuring that those people have opportunities to speak up. As an example, there is evidence from the study of pediatric care that including patients' families and nurses-who are often excluded from physicians' rounds-provides meaningful benefits in the form of better diagnoses and care plan development because these individuals can contribute information not possessed by other team members that can be used in making care decisions [14,15].…”
Section: Expertise Usementioning
confidence: 99%
“…In this way, having a clear understanding of membership can increase the likelihood that people with relevant knowledge will be included in discussions, a necessary first step to ensuring that those people have opportunities to speak up. As an example, there is evidence from the study of pediatric care that including patients' families and nurses-who are often excluded from physicians' rounds-provides meaningful benefits in the form of better diagnoses and care plan development because these individuals can contribute information not possessed by other team members that can be used in making care decisions [14,15].…”
Section: Expertise Usementioning
confidence: 99%
“…13 A possible solution to address time-intensive care coordination needs for CMC include the formation of multidisciplinary teams that conduct family-centered rounds to allow all involved in the care of the complex child, including family, medical staff, and bedside nurses to be included in the decision-making. [17][18][19][20][21] Families are the pediatric patient's main source of support, and offer the health care team valuable information unique to their child which helps in decisionmaking and may positively affect health outcomes. 17 Through meticulous familycentered care coordination, the hospitalist may be able to spend more time at the bedside with the families and patients to make appropriate medical decisions regarding the care of the child.…”
Section: Discussionmentioning
confidence: 99%
“…FCRs improve discharge timeliness 3 and parental understanding of discharge goals. 2 Trainees in this study reported that FCRs reduce the length of stay because FCRs ''put everyone on the same page'' and often include case managers who help with discharge planning.…”
Section: Fcrs Quality and Outcomesmentioning
confidence: 99%